2018
DOI: 10.3889/oamjms.2018.227
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal PCR for Feasible Molecular Diagnosis of Primary Toxoplasmosis in Women Recently Experienced Spontaneous Abortion

Abstract: AIM:The current study aimed to assess the practicability of a simple loop-mediated isothermal amplification (LAMP) about real-time quantitative PCR to diagnose primary toxoplasmosis among high-risk pregnant women.METHODS:Cloned Toxoplasma samples were used to calculate the analytical sensitivity while specificity was assessed using pooled DNA samples extracted from other parasitic stages.RESULTS:Both techniques showed 100% sensitivity and specificity and then applied to detect recent Toxoplasma infection in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Both techniques were then employed to detect recent T. gondii infection in 77/139 IgG negative women who suffered from spontaneous abortion. The result showed that both techniques were positive in eight samples, thus confirming primary Toxoplasma infection [113].…”
Section: Loop-mediated Isothermal Amplificationmentioning
confidence: 60%
See 2 more Smart Citations
“…Both techniques were then employed to detect recent T. gondii infection in 77/139 IgG negative women who suffered from spontaneous abortion. The result showed that both techniques were positive in eight samples, thus confirming primary Toxoplasma infection [113].…”
Section: Loop-mediated Isothermal Amplificationmentioning
confidence: 60%
“…The IAm Toxo was reported to be highly sensitive and robust and gave good results compared to the alternative amplification technologies [112]. The LAMP method has also been used to detect primary Toxoplasma infection in highrisk pregnant women with previous spontaneous abortion history [113]. The clinical sensitivity and specificity of LAMP were compared with quantitative real-time PCR.…”
Section: Loop-mediated Isothermal Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…One study was not analyzed because it did not accurately quantify the number of IgM and IgG positive cases separately [48], and its data were only systematically presented; therefore, 71 papers were included in the meta-analysis. Eight articles were related to the seroprevalence of anti-T. gondii antibodies in women who had spontaneous abortion in present pregnancy [49][50][51][52][53][54][55][56]. Moreover, serologic methods were used in six of these studies [49-52, 55, 56].…”
Section: Study Identification and Selectionmentioning
confidence: 99%
“…Toxoplasma gondii is an obligate intracellular parasite, causing toxoplasmosis in almost all warm-blooded animals and humans worldwide. Toxoplasmosis is a zoonotic disease of serious public health concern (Opsteegh et al, 2015;El Aal et al, 2018). During T. gondii infection, the parasite releases a number of molecules called T. gondii excretory secretory antigen (ESAs) into the surrounding environment, which allows the organism to attack and survive inside the host cell through immunomodulation (Moncada and Montoya, 2012).…”
Section: Introductionmentioning
confidence: 99%